2022
DOI: 10.1002/pat.5778
|View full text |Cite
|
Sign up to set email alerts
|

Cyclotriphosphazene hyperbranched P/N/Si prepared flame retardants improve mechanical properties and flame retardancy of epoxy resins

Abstract: In this study, a cyclotriphosphazene hyperbranched P/N/Si prepared flame retardant (HBPPSi) was synthesized, and the effects of different loadings of HBPPSi on the mechanical properties, thermal stability and flame retardancy of epoxy resin were investigated. The mechanical property studies showed that the addition of HBPPSi could effectively improve the strength and toughness of epoxy resin, in which the strength and toughness of 5% HBPPSi/EP composites were improved by 43% and 59%, respectively. Meanwhile, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…Also, the addition of EP/7‐KDC to the epoxy web resulted in a lesser FIGRA, an indication that KDC had a lesser fire spread rate. The av‐EHC and FIGRA values of EP/7‐KDC were all well below those of EP (29.95 MJ/kg and 5.88 kW/m 2 ·s, correspondingly), and this could be ascribed to the fact that KDC not only emits phosphorus‐containing radicals with extinguishing function and facilitates the forming of a powerful and stable carbon layer with many elements but also enhances the creation of noncombustible gases for combustion 34 …”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…Also, the addition of EP/7‐KDC to the epoxy web resulted in a lesser FIGRA, an indication that KDC had a lesser fire spread rate. The av‐EHC and FIGRA values of EP/7‐KDC were all well below those of EP (29.95 MJ/kg and 5.88 kW/m 2 ·s, correspondingly), and this could be ascribed to the fact that KDC not only emits phosphorus‐containing radicals with extinguishing function and facilitates the forming of a powerful and stable carbon layer with many elements but also enhances the creation of noncombustible gases for combustion 34 …”
Section: Resultsmentioning
confidence: 90%
“…The residues of these carbons can serve as heat isolation barriers and inhibit the transport of heat and oxygen, thus exhibiting a certain condensed phase effect. This is advantageous to increasing the flame retardant performance of EP 34 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DMP, as a cocuring agent, endowed the modified EP composite with better fire safety performance and well-preserved mechanical properties than pure EP. In addition, Figure d and Table S6 exhibited the THR and TSP decline ratios of EP/8DMP and previous EP with P-containing HBPs (EP/P-containing HBPs). ,,,, It could be found that EP/8DMP showed the highest THR and TSP decline ratios of 51.9 and 53.4%, respectively. Therefore, the as-designed EP/8DMP possessed the best fire safety performance among all EP/P-containing HBP composites listed in Table S6.…”
Section: Resultsmentioning
confidence: 91%